Modification of Flow Structure Over a Van Model By Suction Flow Control to Reduce Aerodynamics Drag - Harinaldi, Harinaldi; Budiarso, Budiarso; Warjito, Warjito; Kosasih, Engkos Achmad; Tarakka, Rustan; Simanungkalit, Sabar Pangihutan; Lay Teryanto, I Gusti Made Fredy (UI Scholars Hub, 2012)
Automobile aerodynamic studies are typically undertaken to improve safety and increase fuel efficiency as well as to find new innovation in automobile technology to deal with the problem of energy crisis and global warming. Some car companies have the objective to develop control solutions that enable to reduce the aerodynamic drag of vehicle and significant modification progress is still possible by reducing the mass, rolling friction or aerodynamic drag. Some flow control method provides the possibility to modify the flow separation to reduce the development of the swirling structures around the vehicle. In this study, a family van is modeled with a modified form of Ahmed's body by changing the orientation of the flow from its original form (modified/reversed Ahmed body). This model is equipped with a suction on the rear side to comprehensively examine the pressure field modifications that occur. The investigation combines computational and experimental work. Computational approach used a commercial software with standard kepsilon flow turbulence model, and the objectives was to determine the characteristics of the flow field and aerodynamic drag reduction that occurred in the test model. Experimental approach used load cell in order to validate the aerodynamic drag reduction obtained by computational approach. The results show that the application of a suction in the rear part of the van model give the effect of reducing the wake and the vortex formation. Futhermore, aerodynamic drag reduction close to 13.86% for the computational approach and 16.32% for the experimental have been obtained.